The Effect of Work Facilities, Supervision and Compensation on Employee Performance at the Lubuk Pakam Pratama Tax Service Office - Helmi, Tengku Ahmad; Gultom, Roni Tua; Lubis, Zul Irfan; Surahman; Tarigan, Nur M Ridha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the influence of work facilities, supervision and compensation on employee performance at the Lubuk Pakam Pratama Tax Service Office. The survey method was used with an active sample of respondents. The research results show that work facilities, supervision and compensation significantly influence employee performance. Adequate work facilities increase productivity and job satisfaction. Effective supervision promotes responsibility and accountability. Fair compensation provides motivation and loyalty. The practical implication of this study is the importance of good human resource management in improving organizational performance. Suggestions for future research include involving more variables and larger samples for higher validity.